Metabolism and Nutritional Content of Polychaeta Nereis sp. with Maintenance Salinity and Different Types of Feed - Eko Setio Wibowo; Endah Sri Palupi; I G A Ayu Ratna Puspitasari; Atang Atang (Marine Science Department Diponegoro University, 2019)
Nereis sp. is an invertebrate member of Familia Nereidae, Classis Polychaeta that lives in the estuarin ecosystem as benthic. Nereis sp. is one of the natural foods that can trigger the maturation of shrimp gamete cells up to 70% because they contain high levels of amino acids and unsaturated fatty acids, but the fulfillment of Nereis sp. still rely from nature. That condition encourages the cultivation of Nereis sp., but there is not much information about it. This study aims to determine the metabolic rate and nutritional content of Nereis sp. with different maintenance salinity and feed. This reasearch used immature Nereis sp with two different type of feed, i.e. with vegetable protein and animal protein. They were maintained in three different salinity i.e. 5, 15, and 25 ppt. The results showed that oxygen consumption rate of Nereis sp was affected by salinity of the medium, but was not influenced by the type of feed given. The highest oxygen consumption was observed in Nereis sp. that maintained at 25 ppt. The body protein content is influenced by the salinity and the type of feed given, while the fat content is not affected by the salinity and the feed. The highest protein, fat and carbohydrate content of the body was detected in salinity of 15 ppt and fed with vegetable protein foods.